Silence is not health: feminists and abolitionists voices “all of us are andrea” (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
14 years ago, Andrea López disappeared, a young victim of sexual exploitation by her partner. From that moment on, with numerous actions, some women began to claim and denounce the violence that Andrea suffered. It is necessary to draw a timeline that reflects the trajectory that women are developing to make violence visible. It seeks to recover the voice of women who, from evoking the memory of a young woman, publicly denounce the maneuvers of the patriarchal state. In the city’s public and political agenda, Andrea’s case was slowly included until it became public interest. Knowing the modes of intervention of this feminist collective and the social significance it means for women is a strategy of daily empowerment that this group promotes as gender claims, proposing as input the denunciation and public visibility in the local order with their actions. Las Andreas were able to influence numerous decisions of different institutions that had and have to intervene in the resolution of the case, this capacity was achieved through militancy and activism.
Keywords: feminist collective; gender; public agenda and politics